Immunobiology of visceral leishmaniasis - Nylén, Susanne; Kumar, Rajiv (Frontiers in Immunology, 2012)
Visceral leishmaniasis (VL), commonly known as kala-azar, is caused by Leishmania donovani and Leishmania infantum (Leishmania chagasi in the Americas). These Leishmania species infect macrophages throughout the viscera, and parasites are typically found in the spleen, liver and bone marrow. Patients with active disease typically exhibit marked immunosuppression, lack reactivity to the Leishmania skin test (LST), a delayed type hypersensitivity test, and their peripheral blood mononuclear cells (PBMC) fail to respond when stimulated with leishmanial antigens in vitro. However, most people infected with visceralizing species of Leishmania never develop disease. Understanding immune failure and the underlying immune mechanism that lead to disease as well as control of infection are key questions for research in this field. In this review we discuss immunological events described in human and experimental VL and how these can affect the outcome of infection.